PERAN KOMITE SEKOLAH DI SMP 3 SINJAI BARAT - Rosdiana . A; Faridah Faridah (UNM (Universitas Negeri Makasar), 2022)
The purpose of this study was to describe the role of the school committee at SMP Negeri 3 Sinjai Barat. This research approach is qualitative with descriptive research type. The data collection technique was done by means of observation, interview and documentation. The results of the study found that the role of the school committee has not been implemented according to Permendikbud Number 75 of 2016 concerning school committees. The results show that the role of the school committee in giving consideration in determining and implementing policies has not been maximally implemented in terms of educational policies and programs, RAPBS / RKAS, school performance criteria, criteria for educational facilities, criteria for school cooperation with other parties. The role of the committee in raising funds and other educational resources has not been implemented due to the limited understanding of the school committee regarding its role as a supporter of the financial or school financial aspects, the same thing was found for the aspect of monitoring educational services, the results of the study found that the role of the committee had not been implemented optimally. . The committee has not followed up on complaints, suggestions, criticisms, and aspirations from students, parents / guardians, and the community, this is conveyed directly by the community to the school without going through the school committee.